Microglia in multiple sclerosis – pathogenesis and imaging. Issue 3 (June 2022) - Airas, Laura; Yong, V. Wee
Abstract : Purpose of review: Microglia normally protects the central nervous system (CNS) against insults. However, their persistent activation in multiple sclerosis (MS) contributes to injury. Here, we review microglia activation in MS and their detection using positron emission tomography (PET). Recent findings: During lesion evolution and the progression of MS, microglia activity may contribute to neurotoxicity through the release of pro-inflammatory cytokines, reactive oxidative species, proteases and glutamate. A means to detect and monitor microglia activation in individuals living with MS is provided by positron emission tomography (PET) imaging using the mitochondrial 18-kDa translocator protein (TSPO) ligand. TSPO PET imaging shows increased microglial activation within the normal appearing white matter that precedes radiological signs of neurodegeneration measured by T2 lesion enlargement. PET-detected microglia activation increases with progression of MS. These findings demand the use of CNS penetrant inhibitors that affect microglia. Such therapies may include hydroxychloroquine that is recently reported in a small study to reduce the expected progression in primary progressive MS, and Bruton's tyrosine kinase inhibitors for which there are now eleven Phase 3 registered trials in MS. Summary: Microglial activation drives injury in MS. PET imaging with microglia-specific ligands offer new insights into progression of MS and as a monitor for treatment responses.